GENDER JUSTICE IN INHERITANCE LAW: A COMPARISON OF THE CONCEPT OF PROPORTIONALITY AND THE CONCEPT OF EQUALITY - Ria Sukmawidari; Irbach Nurfatin Mahmud; Wardayani Wardayani; Kurniati Kurniati (Kafa`ah: Journal of Gender Studies, 2026)
The debate regarding gender justice in inheproporitance law arises from differing concepts, namely proportional distribution (2:1) as applied by some laws, while other laws adhere to the principle of equality (1:1). This study aims to analyze both concepts from the perspective of gender justice, while assessing their relevance in the modern social context. The method used is a literature study with a normative-comparative approach, which compares provisions from various legal systems, such as Islamic law, civil law, customary law, and court decisions, and analyzes them through the theory of gender justice and the maqāṣid al-syarī'ah framework. The results of the study show that both concepts have their own contextual justice. Proportionality is more appropriate when the responsibility for maintenance is entirely borne by men, while equality is more appropriate in situations where men and women both play a role in the family economy. This study confirms that gender justice in inheritance law cannot be understood absolutely, but must be viewed relatively in accordance with social realities and the configuration of roles within the family. The impact of this study is to provide a more neutral and comprehensive insight for the development of inheritance law studies within the framework of gender justice. Keyword: Gender, Inheritance law, Proportionality and Equality